Determination of stress-strain relationship based on alkali activator ratios in geopolymer concretes and development of empirical formulations. (February 2023) - Özbayrak, Ahmet; Kucukgoncu, Hurmet; Atas, Oguzhan; Aslanbay, Huseyin Hilmi; Aslanbay, Yuksel Gul; Altun, Fatih
Abstract: Fly ash-based geopolymer has recently gained attention of researchers due to its potential application, as well as being an alternative binder with low emissions compared to ordinary Portland cement (OPC) in concrete production. Studies which are conducted on the design and mechanical properties of structural members produced from fly ash geopolymer concrete (GPC) are very important in terms of increasing the use of this concrete. The aim of this study is to obtain experimental data on the effect of sodium silicate/sodium hydroxide (SS/SH) and alkali activators/fly ash (AA/FA) ratios on the mechanical properties of a low calcium heat-cured fly ash geopolymer. In addition, it is to reveal the similarities and differences of OPC and GPC by comparing the mathematical formulations in existing regulations and concrete models with experimental data. Thus, geopolymer cylinder concrete samples were produced using 15 different mixtures with SS/SH ratios of 1.5, 2.5 and 3.5, while AA/FA ratios of 0.4, 0.5, 0.6, 0.7 and 0.8. At the end of the study, the optimum SS/SH ratio was obtained as 2.5. A decrease in the AA/FA ratio increases the compressive and splitting tensile strength, while an increment increases the ductility and consuming energy. In addition, the relationship between the experimental data and the splitting tensile strength and modulus of elasticity formulations depending on the compressive strength given in other studies and regulations as a part of literature was investigated, and then, two alternative empirical formulations considering the ratios of alkali activators were proposed at the end of the regression analysis. When the stress-strain relationship of OPC concrete models and GPC mixtures were compared, the closest unconfined concrete model for GPC concrete was the Hognestad model.